Dynamic mass transfer of textiles in rotational motions. Issue 5 (8th July 2019) - Li, Wenbin; Jiang, Yunjing; Jiang, Peiqing; Wang, Xin
Abstract : Purpose: The mass transfer of textiles during movement is complicated as the energy consumption (EC) from skin, surface temperature of fabrics together with environment will work synergistically to determine the sensation and comfort of wearer. The purpose of this paper is to reveal the mass transfer in the human-textile-environment dynamic system. Design/methodology/approach: With a simulated hotplate mounted on a rotational testing platform, this paper focuses on the dynamic mass transfer of a fabric so as to simulate the real-time mass transfer of clothing in movements. Findings: It has been found that the EC and surface temperature ( T ) change against testing time, indicating the convex and concave shapes of the EC– t and T – t curves. The initial moisture regain of the fabric, rotational speed of the platform and the fiber materials of the fabric have shown a great effect on the dynamic mass transfer process. Practical implications: Understanding the dynamic mass transfer of textiles will benefit the design of clothing with better comfort and will contribute to the well-being of wearers. Originality/value: This work reveals the dynamic mass transfer of textiles in rotational movements. It contributes a new approach to studying the mass transfer of clothing in real service.